A Study of Factors Affecting Consumer’s Preference on Travel Agencies in Malaysia: Case of Malaysian Students - Yang, Wei (2013)
According to UNWTO’s data, in 2012 there is 7% increase for Asia and Pacific as the fastest growing region for arrivers’ number, equivalent to 15 million more international tourist arrivals compare to the number on 2011. Malaysia was the NO.10 international tourist arrivals destinations around the world, also the most popular destinations in Southeast Asia. Tourism in Malaysia is huge number of tourism practitioners and broad market prospects. The market prosperity in Malaysia does not mean there is no issue in tourism industry. Relative to the tourism agency, tourist’s complaints on travel agency, government Economic Transformation Program ignored the development of the travel industry. And lack of academic research on consumer’s preference on the travel agency. All reason above to make the study feasible and necessary. According to the current situation in Malaysia tourism industry and travel agency, combine with researcher own conditions. We select Malaysia students as research population and sample. Try to examine the key factor among the student that affecting consumer’s preference toward travel agency. And to identify the consumer’s perception in order to effectively construct counter measure plan by travel agency. Based on the research objective, we will be via primary and secondary research to collect date, and using Quantitative, qualitative and Statistical methods to analysis. Finally we will give to our recommend.